TEKNIK FAST CHARGING BATERAI LITHIUM-ION MENGGUNAKAN LOGIKA FUZZY - Amar Anshori; Bambang Siswojo; Rini Nur Hasanah (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2020)
The increasing use of portable electronic equipment uses more and more lithium-ion batteries. Issues that occur from increased use of the battery pose problems such as less capacity, long charging time, and overcharging protection. Some methods of lithium-ion battery charging techniques are commonly used such as Constan Voltage (CV), Constan Current (CC), CC-CV, and reflex charging methods. In this study the fast charging Lithium-ion battery technique uses fuzzy logic to control temperature and voltage during battery charging using the Pulse Width Modulation (PWM) Charging method, the fuzification process used Is Mamdani method with Center Of Gravity (COG) Defuzzification method. It is expected to accelerate the charging without making the battery temperature exceed the maximum limit, as well as the overcharging. The filling results using this fast charger using the fuzzy logic proved to accelerate charging and protect the occurrence of overcharging the battery.